2020
DOI: 10.1186/s12887-020-1990-9
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter investigation of pediatric gastrointestinal tract magnets ingestion in China

Abstract: Purpose: To describe the incidence and management of gastrointestinal tract Buckyball magnets ingestions in a multicenter Chinese pediatric patient population, and discuss the preventive measures. Methods: Medical records of 74 pediatric patients from 9 large Chinese hospitals during the past 10 years, who were diagnosed as buckyball magnets ingestion and got invasive treatment, were retrospectively studied. The follow-up was through telephone and outpatient service to estimate the post-surgery condition. Info… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
2
23
0
4
Order By: Relevance
“…Other commonly ingested foreign bodies include fish bones, pins, button batteries, magnets, household items, food boluses, and many others. They can get stuck anywhere in the gastrointestinal tract, starting from the proximal esophagus to the colon, manifesting in the form of various signs, symptoms, and complications [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other commonly ingested foreign bodies include fish bones, pins, button batteries, magnets, household items, food boluses, and many others. They can get stuck anywhere in the gastrointestinal tract, starting from the proximal esophagus to the colon, manifesting in the form of various signs, symptoms, and complications [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ingestion of magnets is a serious health hazard for children that can lead to grave consequences if not managed promptly. Multiple magnets across the gastrointestinal tract can attract each other, thus attracting different segments of the bowel together [ 3 ]. This can eventually lead to bowel ischemia, enteroenteric fistulas, bowel perforation, and peritonitis [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, in some areas of the USA, the incidence of multiple magnet ingestion has decreased 6 . In China, although there are warning labels on the toy packages, a recent multicenter investigation shown that the incidence of multiple magnet ingestions is increasing 7 . As our data show, the number of patients in 2019 was approximately four times higher than that in 2015.…”
Section: Discussionmentioning
confidence: 99%